2022
DOI: 10.3389/fevo.2022.923166
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of the DICER-like (DCL) Genes From Peach (Prunus persica): A Critical Role in Response to Drought Stress

Abstract: DICER-likes (DCLs) proteins are the core component for non-coding RNA (ncRNA) biogenesis, playing essential roles in some biological processes. The DCL family has been characterized in model plants, such as Arabidopsis, rice, and poplar. However, the evolutionary aspect and the expression mechanism under drought stress were scarce and have never been reported and characterized in one of the most important worldwide cultivated fruit trees, peach (Prunus persica). Eight DCLs genes in the Prunus persica genome we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
2
2
0
Order By: Relevance
“…Our results are also supported by the earlier findings i.e., the activity of DCL2 in A. thaliana was related with temperature (Zhang et al, 2012). Prupe DCL under drought treatment was differentially expressed in peach (Belal et al, 2022). These findings suggest, that the functions of DCL2 are diverse, and further research is needed for exploring the exact functions of VvDCL2.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are also supported by the earlier findings i.e., the activity of DCL2 in A. thaliana was related with temperature (Zhang et al, 2012). Prupe DCL under drought treatment was differentially expressed in peach (Belal et al, 2022). These findings suggest, that the functions of DCL2 are diverse, and further research is needed for exploring the exact functions of VvDCL2.…”
Section: Discussionsupporting
confidence: 91%
“…Upregulation of SsDCL1a/2/3, SsRDR3/6b and SsAGO2b/5a/5c/6b/SsAGO10c [ 46 ], ZmDCL2/3b, ZmAGO4a/4d/7, ZmRDR2/4 [ 48 ], CaDCL1/2/3, CaRDR2/6, and CaAGO2/10b [ 49 ] was observed under drought stress. In our study, four DCLs were significantly upregulated and two (VaDCL2c in DS and VaDCL3 in DR) were downregulated, similar to the expression pattern in peach [ 47 ]. Several AGOs were induced while VaAGO4a was depressed in the DS genotype (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…In pepper, CaDCL1 and CaDCL3 also exhibited a higher expression in flowers [21], and previous studies revealed that the double mutant of dcl1 and dcl3 exhibited a delay in the flowing of Arabidopsis [109]. Additionally, in peach, PrupeDCL3 also showed a high level of expression in flowers [63]. These findings suggest that DCL1 and DCL3 play positive roles in the flower development of plants.…”
Section: Proteins In Fragariamentioning
confidence: 50%
“…For vegetable crops, seven DCLs have been identified in tomato [25], four in pepper [21], six in common bean [61], eight in Brassica napus [33], and eleven in allotetraploid cotton [62]. Moreover, DCLs were also found in the fruit crops, including grape (four DCLs) [22], sweet orange (five DCLs) [23], banana (three DCLs) [24], and peach (eight DCLs) [63].…”
Section: Introductionmentioning
confidence: 99%